A cross-cultural analysis of educational leadership for social justice in Israel and Turkey: meanings, actions and contexts. Issue 2 (4th March 2017) - Arar, Khalid; Beycioglu, Kadir; Oplatka, Izhar
Abstract: The research compares principals in Israel (Jewish and Arab) and Turkey and how they perceive and practice their role in promoting social justice (SJ) in their schools in order to bridge socioeconomic and pedagogic gaps. It poses three questions: (1) How do Turkish and Israeli SJ leaders make sense of SJ? (2) What do SJ leaders do in both countries similarly and differently? (3) What factors facilitate or hinder the work of SJ in both countries? The qualitative study employed in-depth semi-structured interviews to collect the narratives of 11 school principals in Turkey and Israel. A comparative, holistic analysis was employed to identify the principals' perceptions and daily practice of SJ in their schools. The principals reported different sociocultural, national and personal trajectories that shaped their perceptions of SJ, and described strategies used to promote SJ in their daily scholastic policies, processes and practices that meet the school stakeholders' backgrounds and needs.